2D MXene Ti3C2Tx nanosheets in the development of a mechanically enhanced and efficient antibacterial dental resin composite - Hu, Yingzi; Xu, Zhiliang; Pu, Junmei; Hu, Lanping; Zi, You; Wang, Mengke; Feng, Xingmei; Huang, Weichun (Frontiers in Chemistry, 2022)
The bacterial accumulation at the margins of dental resin composites is a main cause of secondary caries, which may further lead to prosthodontic failure. In this regard, this study for the first time incorporated 2D MXene Ti3C2Tx nanosheets (NSs) into epoxy resin at different mass ratios (0, 0.5, 1.0, and 2.0 wt%) by solution blending and direct curing for dental applications. Compared to the pure resin, the as-fabricated MXene/resin composite not only exhibited improved mechanical and abrasive results but also displayed gradually improved antibacterial activity with MXene loading which was further enhanced by illumination in natural light due to the high photothermal efficiency of MXene. In addition, the cytotoxicity result demonstrated that the MXene-modified resin did not cause severe damage to normal cells. This novel MXene/resin nanocomposite could pave the way for new designs for high-performance, multifunctional nanocomposites to effectively protect dental health in daily life.